Community Perception and Participation in Management of Binuanga Mangrove Tracking Tourism, Bolaang Mongondow Utara Regency - Sri Nuryatin Hamzah; Lestari Nuraini Siki; Citra Panigoro (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Community perception and participation are important factors that support the sustainability of tourism in an area. One marine tourism that has just opened in Bolaang Mongondow Utara Regency is the Binuanga Mangrove Tracking tourism. Binuanga Mangrove Tracking tourism certainly has considerable potential to be developed, so the involvement of the Binuanga Village community is very much needed for tourism sustainability. This study aims to determine the perception and participation of the community towards the management of the Binuanga Mangrove Tracking tourism. This research was conducted from December 2021 to April 2022 in the Binuanga Mangrove Tracking tourism area. The method of determining the respondents used are purposive sampling. The number of respondents was 260, spread over four hamlets in Binuanga Village. Community perceptions and participation in the management of the Tracking Mangrove Binuanga Tourism were analyzed using a Likert scale referring to and the results of the category assessment for each question item were posed using five classes. The results showed that the community in the Binuanga Tracking Mangrove tourism area had a very good perception of the management of Tracking Mangrove tourism, with an average value of 1093.98 or 84.15%. Likewise, community participation is in very good criteria, with an average value of 1206.07 or 93%. The high perception and participation of the community towards the management of the Binuanga Tracking Mangrove tourism show that this tourism benefits the community in Binuanga Village.